Aclidinium inhibits human lung fibroblast to myofibroblast transition. Issue 3 (28th September 2011) - Milara, Javier; Serrano, Adela; Peiró, Teresa; Gavaldà, Amadeu; Miralpeix, Montserrat; Morcillo, Esteban Jesús; Cortijo, Julio
Abstract : Background: Fibroblast to myofibroblast transition is believed to contribute to airway remodelling in lung diseases such as asthma and chronic obstructive pulmonary disease. This study examines the role of aclidinium, a new long-acting muscarinic antagonist, on human fibroblast to myofibroblast transition. Methods: Human bronchial fibroblasts were stimulated with carbachol (10 −8 to 10 −5 M) or transforming growth factor-β1 (TGF-β1; 2 ng/ml) in the presence or absence of aclidinium (10 −9 to 10 −7 M) or different drug modulators for 48 h. Characterisation of myofibroblasts was performed by analysis of collagen type I and α-smooth muscle actin (α-SMA) mRNA and protein expression as well as α-SMA microfilament immunofluorescence. ERK1/2 phosphorylation, RhoA-GTP and muscarinic receptors (M) 1, 2 and 3 protein expression were determined by western blot analysis and adenosine 3′-5′ cyclic monophosphate levels were determined by ELISA. Proliferation and migration of fibroblasts were also assessed. Results: Collagen type I and α-SMA mRNA and protein expression, as well as percentage α-SMA microfilament-positive cells, were upregulated in a similar way by carbachol and TGF-β1, and aclidinium reversed these effects. Carbachol-induced myofibroblast transition was mediated by an increase in ERK1/2 phosphorylation, RhoA-GTP activation and cyclic monophosphate downregulation as well as by the autocrine TGF-β1 release, which were effectively reduced by aclidinium. TGF-β1 activated the non-neuronal cholinergic system. Suppression of M1, M2 or M3 partially prevented carbachol- and TGF-β1-induced myofibroblast transition. Aclidinium dose-dependently reduced fibroblast proliferation and migration. Conclusion: Aclidinium inhibits human lung fibroblast to myofibrobast transition.